2022
DOI: 10.3389/fmed.2022.843737
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Relation to the Clinical Outcome of Hospitalized COVID-19 Patients

Abstract: Coronavirus Disease (COVID-19) is a newly emerged infectious disease that first appeared in China. Vitamin D is a steroid hormone with an anti-inflammatory protective role during viral infections, including SARS-CoV-2 infection, via regulating the innate and adaptive immune responses. The study aimed to investigate the correlation between serum 25-hydroxyvitamin D (25[OH]D) levels and clinical outcomes of COVID-19. This was a retrospective study of 126 COVID-19 patients treated in NMC Royal Hospital, UAE. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Although the reported findings by Hafez et al ( 1 ) could be partly explained by the protective immunomodulatory effects of vitamin D ( 7 ), also DBP might exert its influence on the outcome of COVID-19 patients. In addition to its unique sterol binding ability and its influence on the concentration of vitamin D metabolites, DBP performs a number of critical biological tasks such as actin scavenging, chemotaxis, macrophage activation, and fatty acid transport, which might explain these observations ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the reported findings by Hafez et al ( 1 ) could be partly explained by the protective immunomodulatory effects of vitamin D ( 7 ), also DBP might exert its influence on the outcome of COVID-19 patients. In addition to its unique sterol binding ability and its influence on the concentration of vitamin D metabolites, DBP performs a number of critical biological tasks such as actin scavenging, chemotaxis, macrophage activation, and fatty acid transport, which might explain these observations ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The observed link between vitamin D deficiency and poor clinical outcomes among COVID-19 patients in the paper of Hafez et al ( 1 ) could be influenced by DBP and its polymorphism. In a previous study, we looked at the impact of DBP phenotypes in patients with a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection.…”
Section: Vitamin D Binding Protein Phenotypes and Covid-19mentioning
confidence: 94%
See 1 more Smart Citation
“…While Controversies still persist concerning the plausible role of Vitamin D in COVID-19 disease severity and effect on the outcome; our study demonstrated a significant correlation between severe Vitamin D Deficiency and the risk of a poor disease outcome. We observed a significant link between severe vitamin D deficiency, ICU admission, and COVID-19-related in-hospital mortality (2).…”
Section: Introductionmentioning
confidence: 66%
“…Indeed, cohort studies reported lower VitD levels in SARS-CoV-2-infected patients than in SARS-CoV-2-negative subjects, suggesting a relationship between insufficient VitD levels and SARS-Cov-2 infection [ 5 ]. Interestingly, low VitD levels were also associated with a more severe course of the disease [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%